The consequences of Brexit for Africa: The case of the East African Community - Andrew Mold (Journal of African Trade, 2018)
How will Brexit impact on Africa? This paper looks at the available empirical evidence and carries out a Computable General Equilibrium simulation, focusing particularly on the prospects for the East African Community (EAC). The paper makes three main points. First, while the direct impacts through investment, trade and remittances are likely to be relatively small, African countries may benefit from the creation of new export opportunities. However, these are mainly in resource-intensive sectors that are not considered a priority for the development agendas of most African countries. Second, indirect consequences, through Brexit's impact on the global economy, its influence on the Economic Partnership Agreements (EPAs) with the European Union, or a potential reduction in UK development cooperation, are likely to be equally important over the longer run. Finally, one overlooked consequence of Brexit for Africa is that it could undermine confidence in "deep" regional integration processes like the EAC. The paper concludes that the correct response at such a time is not to falter but to redouble efforts towards regional integration through the implementation of the recently-signed African Continental Free Trade Area, while learning the pertinent lessons from Europe.
Keywords: 330; Brexit; East African Community (EAC); Computable general equilibrium model; Regional integration; Trade